The Magnetic Urtext: Restoration as Music Interpretation - Canazza, Sergio; Schubert, Emery; Chmiel, Anthony; Pretto, Niccolò; Rodà, Antonio (Frontiers in Psychology, 2022)
This paper discusses a range of issues in the restoration and preservation of tape music and calls for urgent action. A detailed program of research and restoration is proposed. We also present some of the issues and controversies that must be considered and approaches we have applied in the preservation of tape music, highlighting how these interpretations can impact later performances (playback) of these tape documents. Fundamentally, we argue that the act of tape music restoration has a parallel with the interpretation of the “Urtext score” in the performance of music from the Common Practice Era.